CMET-02. ESTABLISHING THE SAFETY AND EFFICACY OF A NEW MULTI-AGENT INTRATHECAL TREATMENT PROTOCOL FOR PATIENTS WITH NEOPLASTIC MENINGITIS. (11th November 2019) - Zammar, Samer; Eby, Richard; Zacharia, Brad; Strowd, Roy; Grossman, Stuart; Aregawi, Dawit; Michael, Glantz
Abstract: BACKGROUND: The prognosis for neoplastic meningitis (NM) remains dismal and single-agent (rather than multi-agent) chemotherapy remains the standard of care. Objective: To analyze survival of patients with NM receiving multi-agent vs. single-agent intrathecal chemotherapy and evaluate the safety of antitumor intrathecal biological agents. METHODS: We compared a standardized multi-agent intrathecal treatment cohort to the corresponding patient level data acquired from 6 of the 7 randomized controlled trials (RCTs) conducted in patients with NM, all of which used single-agent intraventricular therapies. The toxicity of intrathecal biological agents was studied by analyzing the outcome data form patients with NM treated with at least 1 intrathecal biological drug. RESULTS: 283 patients receiving multi-agent therapy were compared to 290 patients from the RCTs. Patients and tumor characteristics did not differ between groups. All patients from the multi-agent patient group were included in an intent-to-treat model. For all solid tumors, median survival (multi-agent vs. single-agent treatment) was 211 vs. 97 days, hazard ratio (HR) 3.39, p< 0.001. For lymphoma, survival was 304 vs. 81 days, HR 2.10, p< 0.001. Stratified by tumor histology, median survival for breast cancer NM was 315 days [95% CI 248–449], for lung cancer 193 days [127- 200]; for melanoma 307 days [65–1492], and for primary brain tumors 253 days [187- 348]. No additional toxicity was seen in the multi-agent compared to the single-agent treatment groups. In 110 patients, grade III toxicity occurred in 5.3%, 3.1%, 0% and 0% of patients receiving rituximab, trastuzumab, panitumumab, and alpha interferon. No difference in survival was seen when comparing patients with and without treatment related toxicity in any histological groups. CONCLUSION: Multi-agent intraventricular chemotherapy was associated with dramatically increased survival in patients with solid tumor and lymphomatous NM. Incorporating biologic agents as part of a multi-agent intrathecal treatment regimen is very safe.